National trends in off-label use of atypical antipsychotics in children and adolescents in the United States. Issue 23 (June 2016) - Sohn, Minji; Moga, Daniela C.; Blumenschein, Karen; Talbert, Jeffery
Abstract : Abstract: The objectives of the study were as follows: to examine the national trend of pediatric atypical antipsychotic (AAP) use in the United States; to identify primary mental disorders associated with AAPs; to estimate the strength of independent associations between patient/provider characteristics and AAP use. Data are from the National Ambulatory Medical Care Survey and the National Hospital Ambulatory Medical Care Survey. First, average AAP prescription rates among 4 and 18-year-old patients between 1993 and 2010 were estimated. Second, data from 2007 to 2010 were combined and analyzed to identify primary mental disorders related to AAP prescription. Third, a multivariate logistic regression model was developed having the presence of AAP prescription as the dependent variable and patient/provider characteristics as explanatory variables. Adjusted odds ratios (AORs) with associated 95% confidence intervals (CIs) were estimated. Outpatient visits including an AAP prescription among 4 to 18-year-old patients significantly increased between 1993 and 2010 in the United States, and over 65% of those visits did not have diagnoses for US Food and Drug Administration-approved AAP indications. During 2007 to 2010, the most common mental disorder was attention-deficit hyperactivity disorder, accounting for 24% of total pediatric AAP visits. Among visits with attention-deficit hyperactivity disorder diagnosis, those with Medicaid as payer (AOR 1.66, 95% CI 1.01–2.75), comorbid mental disorders (e.g., psychoses AOR 3.34, 95% CI 1.35–8.26), and multiple prescriptions (4 or more prescriptions AOR 4.48, 95% CI 2.08–9.64) were more likely to have an AAP prescription. The off-label use of AAPs in children and adolescents is prevalent in the United States. Our study raises questions about the potential misuse of AAPs in the population.